catena-Poly[copper(II)-bis(μ-2-ethyl-5-methylimidazole-4-sulfonato-κ(3) N (3),O (4):O (4′))] - Purdy, Andrew P. (International Union of Crystallography, 2011)
In the title compound, [Cu(C(6)H(9)N(2)O(3)S)(2)](n), the copper(II) ion sits on an inversion center and is chelated by the imidazole N and sulfonate O atoms of two ligands in equatorial positions. O atoms of adjacent molecules coordinate in the axial positions. Jahn–Teller tetragonal distortion is evident in the coordination geometry [Cu—N and Cu—O equatorial distances of 1.971 (3) and 2.045 (2) Å, respectively, with a Cu—O axial distance of 2.433 (3) Å]. The structure is propagated by an infinite chain of eight-membered (Cu—O—S—O)(2) ring systems along the a axis. Only N—H⋯O hydrogen bonding exists between the chains.